Cryoballoon Pressure Waveform Change during Balloon Inflation is not a Reliable Predictor of Adequate Pulmonary Vein Occlusion. Issue 12 (19th September 2014) - SAFAVI‐NAEINI, PAYAM; SHANOON, FARAH; NAZERI, ALIREZA; RASEKH, ABDI; SAEED, MOHAMMAD; RAZAVI, MEHDI; MASSUMI, ALI
<x xml:space="preserve">Abstract</x> Background Cryoballoon ablation of pulmonary veins (PVs) is widely used to treat atrial fibrillation (AF). Successful ablation requires occluding the PVs by cryoballoon. Angiography is a standard method of assessing PV occlusion. To decrease contrast doses and overcome potential contraindications (e.g., allergy to contrast, renal disease), alternative methods have been tested, including intracardiac echocardiography, transesophageal echocardiography‐color flow Doppler, and distal cryoballoon pressure monitoring. Objective We evaluated pressure monitoring's accuracy in detecting PV occlusion during cryoballoon ablation. Methods We studied 72 PVs in 18 nonconsecutive patients (mean age 68 ± 8 years; 13 male) who underwent cryoballoon ablation for paroxysmal AF. In 67 PVs, we documented the point at which the recorded pressure waveform at the distal tip of the inflated cryoballoon transformed from a left atrial into a pulmonary arterial pressure waveform. PV occlusion was confirmed by concurrent PV angiography through the distal balloon channel. Occlusion was rated on a I–IV scale in which I indicated poor occlusion with major leakage and IV indicated complete occlusion without leakage. Results In 43 of 67 PVs (64%), the change in the pressure waveform from left atrial to pulmonary arterial was associated with complete PV occlusion (grade IV), confirmed by angiography. In the other 24 PVs, complete occlusion was achieved by further movement of the cryoballoon under intracardiac echocardiographic guidance and angiographic confirmation. All 67 PVs were electrically isolated with cryoballoon. Conclusions The change in pressure waveforms at the distal tip of inflated cryoballoon is not a reliable predictor of complete PV occlusion during cryoballoon ablation.